SOSIALISASI PEMANFAATAN INTERNET UNTUK PENDIDIKAN PADA PELAJAR SMK AL-MADANI PONTIANAK - Menur Wahyu Pangestika; Yulrio Brianorman (Jurnal Buletin Al-Ribaath, 2017)
Nowadays internet usage can not be denied has become a requirement of many people, where internet can become source of knowledge or global information giver as well as source of income. This activity is intended to find out what students of SMK Al-Madani Pontianak about the utilization of internet for education by giving insight on internet problem for education which is used as instructional media, giving insight on UU Informasi dan Transaksi Elektronik (Undang Undang No 19 Tahun 2016) and about Internet CAKAP. This activity is done by way delivery of materials, giving questioner divided into two sessions, giving questioner before the material and after the material. At the end of the activity, the leaflets are distributed to give students insight into the internet for education that discusses the knowledge about the internet, its utilization and some educational sites. From the results of tests on 32 students who fill the questioner, visible students SMK AL-Madani about the understanding of the internet is 66%. After the socialization, thoroughly they increased to 89%. Income tax benefits. From the calculation results can be known existence. Keywords: Healthy Internet, Students of SMK Al-Madani, Socialization